An Analysis of Teacher Efficacy and Perspectives about Elementary Literacy Instruction - Joy Abernathy-Dyer; Evan Ortlieb; Earl H Cheek (Arizona State University, 2013)
At the core of every teacher is a set of beliefs and knowledge regarding teaching and learning. As a teacher develops her expertise, curricular practices are refined and self-efficacy is enhanced. Teachers possess varying degrees of efficacy and perceptions that impact literacy instruction within their classrooms. Yet, often times they are mandated to teach in certain ways to achieve desirable student outcomes, even when they may not agree with the methods or processes wholeheartedly. The purpose of this study is to explore some of the issues that change teachers' instructional practices in the classroom and to reveal some of the issues that influence as well as hinder instructional reform within that setting. This qualitative case study uses observations, interviews, and questionnaires to highlight teacher efficacy from four first-grade teachers. Testing data indicate students achieve both because of instruction and teachers' willingness to implement the reading program with fidelity. Findings from this study can assist in setting up professional development, serving as a guide for providing warranted support for student learning and teacher knowledge, and fostering considerations for including teachers in the important stages regarding the planning and implementation of classroom literacy instruction.